Spontaneously Diabetic Torii (SDT) Fatty Rat, a Novel Animal Model of Type 2 Diabetes Mellitus, Shows Blunted Circadian Rhythms and Melatonin Secretion - Katsuya Sakimura; Tatsuya Maekawa; Shin-ichi Kume; Takeshi Ohta (International Journal of Endocrinology)
In patients with diabetes mellitus (DM), impairments of circadian rhythms, including the sleep–wake cycle, blood pressure, and plasma melatonin concentrations, are frequently observed. Animal models of DM are also reported to show aberrant circadian rhythms. However, the changes in the circadian rhythms of plasma soluble substances, including melatonin, in diabetic animals are controversial. In the present study, we investigated the circadian rhythms of spontaneous locomotor activity, metabolic parameters (plasma glucose, triglyceride, and total cholesterol), and plasma melatonin concentrations in Spontaneously Diabetic Torii (SDT) fatty rats, a novel animal model of type 2 DM. Although SDT fatty rats exhibited low locomotor activity in the dark phase, no phase shifts were observed. The circadian variations of plasma metabolic parameters were more apparent in the SDT fatty rats compared with control Sprague–Dawley (SD) rats. The circadian rhythms of plasma melatonin concentrations were significantly impaired in SDT fatty rats. To get an insight into the mechanism underlying the impaired melatonin secretion in SDT fatty rats, the expression of arylalkylamine N-acetyltransferase (Aanat) and acetylserotonin O-methyltransferase (Asmt) mRNA, which encode the rate-limiting enzymes for melatonin synthesis, was investigated in the pineal gland. There were no significant differences in Aanat and Asmt expression between the control SD and SDT fatty rats. These results suggest that SDT fatty rats show impaired circadian rhythms and dysregulated melatonin secretion.